O helenismo e o judaísmo tardio, influências helenísticas no documento “O testamento de Salomão” - São Mateus, Juliano Gonzaga (2017)
Solomon's testament is a document that tells the construction of the temple of Solomon and the power that it had on the demons, in his narrative it is possible to observe the influence of the Jewish culture and mainly of the Hellenic one. Hellenism is the rise of Greek culture consolidated by Alexander the Great and propagated throughout its Empire, this culture was so strong that it was able to influence several others, including Judaism and the document itself. In this article we will present the aspects of Hellenism in the "Testament of Solomon"